1982
DOI: 10.1142/s0192415x82000117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Serum Cortisol Level and Dopamine Beta-hydroxylase Activity in Normal Chinese

Abstract: Serum cortisol levels were determined in 40 normal Chinese and dopamine beta-hydroxylase activities were measured in 22 normal subjects before and after acupuncture treatment. All subjects were studied twice with an interval of one week or more. In the self-control study, the subjects were needled at 5 non-acupuncture loci. In the experimental study, they were needled at the following 5 traditional acupuncture loci--right side GB-20, both sides EH-6, and both sides St-36. Blood samples were withdrawn before ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Collectively, these studies corroborate our finding that EA works differently in healthy than in pathological conditions. Others have reported, however, that acupuncture increased serum levels of cortisol in healthy humans and horses [13,14]. This discrepancy may be due to differences in the subjects used in the studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Collectively, these studies corroborate our finding that EA works differently in healthy than in pathological conditions. Others have reported, however, that acupuncture increased serum levels of cortisol in healthy humans and horses [13,14]. This discrepancy may be due to differences in the subjects used in the studies.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies on uninjured animals reported that acupuncture increases adrenocorticotropic hormone (ACTH) [11,12] and glucocorticoid [13][14][15]. Since adrenal glands secrete glucocorticoids such as cortisol in humans [13]and horses [14] and corticosterone (CORT) in rabbits [15], these studies suggest that EA may activate the adrenals to increase glucocorticoid secretion, leading to suppression of inflammatory responses.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies on uninjured animals reported that acupuncture increases adrenocorticotropic hormone (ACTH) [11,12] and glucocorticoid [13-15]. Since adrenal glands secrete glucocorticoids such as cortisol in humans [13]and horses [14] and corticosterone (CORT) in rabbits [15], these studies suggest that EA may activate the adrenals to increase glucocorticoid secretion, leading to suppression of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed, including mechanisms involving the hypothalamus-pituitary-adrenal (HPA) axis, the autonomic nervous system, and brain derived neurotrophic factor [12]. Electroacupuncture may result in release of β-endorphin and corticotrophin into the peripheral blood [35] and lead to increased serum cortisol levels [36]. Activation of the hypothalamus and limbic system after acupuncture has been demonstrated on functional magnetic resonance imaging (fMRI) [37].…”
Section: Discussionmentioning
confidence: 99%